Surface and subsurface analysis of TC18 titanium alloy subject to longitudinal-torsional ultrasonic vibration-assisted end milling - Xie, Weibo; Wang, Xikui; Zhao, Bo; Li, Guangxi; Xie, Zhijiang (Journal of alloys and compounds, 2022)
Longitudinal-torsional ultrasonic vibration-assisted milling is a machining method that can effectively improve the quality of the machined surface. When this method is used for the end milling of TC18 titanium alloy, however, the law of influence on the machined surface and subsurface remains unclear. In this study, we examined the effects of the ultrasonic amplitude, feed rate, and cutting speed on the machined surface morphology, roughness, surface residual stress, and subsurface microstructure in the longitudinal-torsional ultrasonic vibration-assisted end-milling process. According to the results, longitudinal-torsional ultrasonic vibration-assisted end milling can help form more obvious surface microtextures with a more distinct surface texture regularity at large amplitude, small feed rate, and high cutting speed. Compared with conventional milling, longitudinal-torsional ultrasonic vibration-assisted milling generates a larger roughness and surface residual stress and a deeper plastic deformation layer of the subsurface in the case of an obvious highly perturbed layer. In addition, the surface residual stress becomes greater and the plastic deformation layer gets deeper at a larger amplitude. When the amplitude was 5 µm, the surface residual stress was − 450.625 MPa and the depth of the deformation layer was 5.4 µm. The stress and depth increased by 21.55 % and 134.78 %, respectively, compared with those of conventional milling. The increase in the feed rate enhanced the roughness, decreased the surface residual stress, and did not significantly alter the depth of the plastic deformation layer. When the feed rate was 0.01 mm/z, the roughness was 0.383 µm and the surface residual stress was − 479.1 MPa. The feed rate and roughness increased by 42.63 % and 20.62 %, respectively, compared with those of conventional milling. With the increase in the cutting speed, the roughness increased, and the surface residual stress and the depth of the plastic deformation layer decreased. When the cutting speed was 15 m/min, the roughness was 0.31 µm, the surface residual stress value was − 454.7 MPa, and the depth of the plastic deformation layer was 5.7 µm. These three parameters increased by 17.8 %, 18.79 %, and 92.5 %, respectively, compared with those of conventional milling. This research has certain application prospect in surface machining of titanium alloy and quality control of machined surface. [Display omitted] •Low feed and high cutting speed could form more regular surface texture.•Ultrasonic milling may increase the surface residual compressive stress.•Ultrasonic milling can produce strong plastic deformation in the subsurface